Figurative Language in Novel The Notebook and The Host - Rita Napitupulu; Jessica Rusli (Journal of Language, Literature and Teaching, 2019)
This study was aimed at describing the types of figurative language used in two genres; they were romance (The Notebook) and science fiction (The Host) and the reasons underlying the finding. This research was conducted by using descriptive qualitative design which relied on words to describe the phenomena. The data was analyzed by using Miles et.al „s interactive model of data analysis. Based on the analysis, it can be concluded that simile, hyperbole, metaphor, and personification existed in both of the genres. The reasons underlying this finding were to create tone and communicate emotion, to create humor and abstract thinking, and cultural cohesiveness. These reasons were tied to both the romance and also science-fiction genre.